Microbially influenced corrosion - Any progress? - Little, B.J.; Blackwood, D.J.; Hinks, J.; Lauro, F.M.; Marsili, E.; Okamoto, A.; Rice, S.A.; Wade, S.A.; Flemming, H.-C. (Elsevier, 2020)
Microbially influenced corrosion (MIC), is acknowledged to be the direct cause of catastrophic corrosion failures,with associated damage costs ranging to many billions of US$ annually. In spite of extensive research andnumerous publications, fundamental questions relating to MIC remain unanswered. The following review pro-vides an overview of current MIC research and stresses the lack of information related to MIC recognition,prediction and mitigation. The review establishes a link between management decisions and root causes. Aholistic, proactive approach to MIC is suggested in which an entire system is considered, monitored and im-proved.
Keywords: Microbially influenced corrosion; Paint coatings; Cathodic protection